2020
DOI: 10.3390/agriculture10050158
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Organic Amendments on Soil Properties and Maize (Zea maize L.) Growth

Abstract: In recent years, the application of biochar as soil amendment has generated a huge interest for the preservation of soil fertility by improving the physicochemical and biological properties of soil, and for the reduction of the negative effects of greenhouse emissions (climate-change adaptation). In this study, we investigated the effect of three soil amendments, namely, biochars derived from wood (BC), solid digestate (SD), and biochar derived from solid digestate (BSD), on soil parameters and their influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The synergistic application of PGPR and biochar had a highly positive effect on physiological traits, plant growth, and yield-related traits in comparison to sole application and control treatment. The improvement in plant development might be attributed to the biosynthesis of phytohormones, like IAA, which could essentially be linked to the yield and its components [ 58 ], increasing nutrients [ 48 , 59 , 60 ], the activity of 1-aminocyclopropane-1-carboxylate (ACC) deaminase, and osmolyte production [ 41 , 61 ]. Our findings showed that singular application of biochar significantly enhanced the growth, physiology, and productivity of maize compared with PGPR and non-treated control.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic application of PGPR and biochar had a highly positive effect on physiological traits, plant growth, and yield-related traits in comparison to sole application and control treatment. The improvement in plant development might be attributed to the biosynthesis of phytohormones, like IAA, which could essentially be linked to the yield and its components [ 58 ], increasing nutrients [ 48 , 59 , 60 ], the activity of 1-aminocyclopropane-1-carboxylate (ACC) deaminase, and osmolyte production [ 41 , 61 ]. Our findings showed that singular application of biochar significantly enhanced the growth, physiology, and productivity of maize compared with PGPR and non-treated control.…”
Section: Discussionmentioning
confidence: 99%
“…Unagwu et al (2021) reported an increase in soil pH after application of animal (chicken, cow, and pig) manure at 15 t ha −1 compared to the control treatment. Calamai et al (2020) found a significant effect on soil pH after organic amendment application. A positive effect of animal manure in neutralising soil acidity has been reported (Han et al, 2016;Du et al, 2020;Rayne, Aula, 2020;Ferreira et al, 2022).…”
Section: Resultsmentioning
confidence: 90%
“…crease soil fertility [4][5][6][7] as well as provide economic benefits [8,9]. Analysis of the topsoil carbon balance indicates that approximately 40% of the carbon-rich biochar appears to have been lost through mineralization, erosion, or vertical displacement [10].…”
Section: Of 16mentioning
confidence: 99%